A selective CB2R agonist (JWH133) protects against pulmonary fibrosis through inhibiting FAK/ERK/S100A4 signaling pathways - Xiao Wu; Lina Chen; Yiju Cheng; Yuquan Zhang; Wenting Yang; Lin Pan; Chenkun Fu; Honglan Zhu; Menglin Zhang (BMC Pulmonary Medicine, 2023)
Abstract Background The combination of the endocannabinoid system (ECS) and the type 2 cannabinoid receptor (CB2R) can activate various signal pathways, leading to distinct pathophysiological roles. This interaction has gained significant attention in recent research on fibrosis diseases. Focal adhesion kinase (FAK) plays a crucial role in regulating signals from growth factor receptors and Integrins. It is also involved in the transformation of fibroblasts into myofibroblasts. This study aims to investigate the impact of the CB2R agonist JWH133 on lung fibrosis and its potential to alleviate pulmonary fibrosis in mice through the FAK pathway. Methods The C57 mice were categorized into five groups: control, BLM, BLM + JWH133, BLM + JWH133 + NC, and BLM + JWH133 + FAK groups.JWH133 was administered to mice individually or in conjunction with the FAK vector. After 21 days, pathological changes in mouse lung tissues, inflammatory factor levels, hydroxyproline levels, and collagen contents were evaluated. Moreover, the levels of the FAK/ERK/S100A4 pathway-related proteins were measured. Results JWH133 treatment decreased inflammatory factor levels, attenuated pathological changes, and reduced extracellular matrix accumulation in the mouse model of bleomycin-induced pulmonary fibrosis; however, these effects were reversed by FAK. JWH133 attenuated fibrosis by regulating the FAK/ERK/S100A4 pathway. Conclusions The results presented in this study show that JWH133 exerts a protective effect against pulmonary fibrosis by inhibiting the FAK/ERK/S100A4 pathway.Therefore, JWH133 holds promise as a potential therapeutic target for pulmonary fibrosis.